(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The primary function of Insolvency law is to have a timely and effective resolution of the rights of the stake holders and unlocking the asset value of the corporate debtor before eroding the value so that all the stake holders will get the maximum share out of the value. In our Country real estate industry has shown magnificent growth thanks to the support of banks and financial institutions in providing project loans as well as individual home loans. Earlier the real estate industry was unregulated, and the terms and conditions were fixed by the builders unilaterally which needs to be accepted by Individual home buyers. The trend was changed with introduction of RERA Act. As per the provisions of RERA read with the bipartite agreement entered between the builder and buyer the home buyers has a dual remedy i.e. either to receive the property that it had paid for or to have the money returned to them with interest. Now in addition to RERA act the home buyers are empowered under the IBC to have their voice heard in CoC meetings and their rights recognized as financial creditors. The amendments to IBC made in the year 2020 and 2022 is very laudable and it recognized the rights of home buyers. In this paper we analyze the evolution of rights of home buyers under IBC and what are the additional empowerment that is required for the home buyers.